As atividades de enriquecimento curricular: a voz dos atores - Ferreira, Maria Filomena Gonçalves (2018)
Changes on family structure and social life requires a reformulation on the pedagogic organization, which is related to full time school programmes and the opportunity of choice on several Curricular Enrichment Activities (CEA) within primary schools. The implementation of this programme, obliges to re think and reorganize schools, englobing new dimensions to staff workload. This information results from an investigation, integrated on Master of Education Sciences, specialized on School Organization and Administration, in order to identify perceptions and expectations from head teachers, general teachers and parents. This qualitative research study involved the use of interviews, surveys, studying documents and content analysis. The study results suggests that the CEA model applied has being frequently attended and very welcomed by the majority of the participants, as well as, the valorisation of new learning needs and a particularly unique articulation between curricular and pedagogic point of view. There are three aspects to highlight: CEA timetable, the amount time spent by children at school and the need of organizational work conditions, to articulate teacher’s school workload.